PEMBERDAYAAN “TEACHER-PARENT PARTNERSHIP” UNTUK MENINGKATKAN PARTISIPASI PESERTA DIDIK KELAS XI IPA 1 SMA NEGERI 7 YOGYAKARTA - Reni Herawati (Jurnal Ilmiah Guru Caraka Olah Pikir Edukatif, 2014)
This paper presents the writer’s experience in implementing a learning approachto build students’ motivation by empowering parental partnership. TeachingEnglish, especially, at class XI IPA 1, SMA N 7 Yogyakarta, is very challenging.However, the writer as the teacher found some problems in learning process. Itwas her task to create an effective learning process, therefore, she had to managethe class into active and motivated classes. The class consisted of 24 students whowere commonly silent and passive. Their class participation especially in speakingclass was far from the expected. This had led the writer to make an effort to fid alearning approach to be implemented in her speaking class. The writer performedan approach by Empowering “Teacher-Parent Partnership” to Enhance ClassParticipation among Students of XI IPA 1 at SMA Negeri 7 Yogyakarta. This paperwas aiming at describing the effectiveness of “Teacher-Parent Partnership” as anapproach to enhance students’ participation and explaining how it could enhancespeaking capability among the students of SMA N 7 Yogyakarta.The writer was really sure that parents’ involvement in children’s education ishighly correlated with children success at school. She took a deep concern sinceshe found that the teacher-parent partnership, so far, was only done but to makecommunication about school fee, regulation, and school programs. Meanwhile, onlyfew teachers realize that personal communication between teacher and parents,especially about the progress of the children at class, was very important. The writerwas really sure that parents’ involvement was needed; she decided to empowerparental partnership to build the students’ motivation.The implementation of empowering teacher-parent partnership used severalways of communication: 1) email and letter, 2) news-letter, 3) telephone, 4) meeting.Some valuable fidings were proven. The communication between teacher and parentled a new atmosphere in the class. Among students, teachers and parents could becloser. It gave an amazing power to build students’ motivation. They were creatingconducive class. They were getting better gradually in English learning. In a nutshell, “Empowering Teacher-Parent Partnership” was proven to be an effectiveapproach to solve the problems of lack participation at Class XI IPA 1, SMAN 7Yogyakarta and to enhance the students’ competence of speaking.Key words: teacher-parent partnership, learning approach, students’ participation,Key words:English learning